Determinants of the Joint Adoption of Climate-Smart Agriculture Practices by Agro-Pastoralists in Sokoto State, Nigeria - Oladele, Oladimeji; Yakubu, Danlami; Oladele, Olamide (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2025)
This study examined the determinants of the joint adoption of climate-smart agriculture practices by agro-pastoralists in Sokoto State, Nigeria. A multi-stage sampling technique was used to select 428 agro-pastoralists who were surveyed using a structured questionnaire. The data were subjected to multivariate probit, ordered probit regression, and factor analysis. The climate-smart practices considered were water, nutrients, carbon, the weather, and crop-smart activities. The results show that the majority of the agro-pastoralists were male (85%), married (90%), and had formal education (55%). The mean score for age, farming experience, household size, and farm size was 44.81 years, 22.26 years, 10.25 persons, and 7.33 hectares, respectively. The multivariate model revealed that land tenure, extension contact, awareness of climate incidences, farming systems, sources of credit, gender, perception, and association membership significantly influenced the joint adoption of climate-smart agricultural practices. This study advocates that resources and conditions that promote the joint adoption of climate-smart practices should be identified to facilitate the dissemination and effective adoption of technologies.